EXPERIMENTAL INVESTIGATION ON TERNARY BLENDED CEMENT MORTAR - Ramkumar, M.; .Kooteeswaran, Mr.G.T (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The manufacture of Portland cement is environmentally unfriendly because for each ton of cement produced, approximately the same amount of CO2, in addition to this, CH4 and NO, which are major greenhouse gases, are released into the atmosphere are also released into the atmosphere. Investigations have revealed that, replacing part of Portland cement by industrial by-products such as blast furnace slag and fly ash in cement mortar can contribute significantly to the reduce the emission of these greenhouse gases and also save energy. This study investigates the use of considerable volume of blended cement (Portland Pozzolana and Portland Slag Cements i.e. PPC & PSC) as the partial replacement for 53 Grade OPC in cement mortar. Investigations are carried out on 1:3 ratio of cement mortar with a water-cement ratio of 0.5. The percentage replacement of OPC varies combination to the control about 60%. A total of 168 specimens of the PPC/PSC/OPC mortar were cured in cubes of 70.7mm dimension for 28 days and the compressive strength and density determined. The results of the present investigation clearly indicate that the performance of blended cement mortar is better than that observed for 53 grade OPC cement mortar.